A Quadratic Triangular Finite Volume Element Method for a Semilinear Elliptic Equation. Issue 1 (11th October 2016) - Xiong, Zhiguang; Deng, Kang
Abstract: In this paper we extend the idea of interpolated coefficients for a semilinear problem to the quadratic triangular finite volume element method. At first we introduce quadratic triangular finite volume element method with interpolated coefficients for a boundary value problem of semilinear elliptic equation. Next we derive convergence estimate in H 1 -norm, L 2 -norm and L ∞ -norm, respectively. Finally an example is given to illustrate the effectiveness of the proposed method.